ДАВИН ТУЛТУЙСКОГО ЛАЗУРИТОВОГО МЕСТОРОЖДЕНИЯ (ПРИБАЙКАЛЬЕ) - Сапожников А.Н.; Чуканов Н.В.; Суворова Л.Ф.; Феоктистова Л.П.; Богданова Л.А. (My University, 2006)
Water-bearing СОз-davyne discovered at the Tultuy lazurite deposit, Baikal region, was investigated by the IR spectroscopy, electron microprobe and X-ray diffraction methods. The mineral is characterized by relatively low contents of chlorine and potassium (2.0 and 0.13 apfu, respectively) and the lower values of hexagonal unit cell parameters (a = 12.674, с = 5.316 A). Crystal-chemical features (including the stated of water and additional anions) of davyne from Tultuy, as compared with other members of the cancrinite group, allow concluding that the studied mineral is a facial analogue of cancrinite-type minerals. It was formed at the final stage of the lazurite formation process, at high activity of chlorine and low activity of sulphur.